2018
DOI: 10.3169/mta.6.64
|View full text |Cite
|
Sign up to set email alerts
|

[Invited Paper] Recent Advances in Biometric Recognition

Abstract: This paper presents recent advances in biometric recognition, where we focus on face, fingerprint and iris recognition, which are major research topics on biometric recognition. We summarize the research trend of face, fingerprint and iris recognition over the past decade. This paper also presents our activities of biometric recognition. Our approach employs the phase information obtained by Discrete Fourier Transform (DFT) of images. The phase information preserves the inherent features of the image, and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Ito et al [17] commented on how researchers seek "new biometric traits to enhance the accuracy and convenience of biometric recognition" suggesting that modalities differ in their performance. Each modality is unique and with that brings an assortment of 'influencing factors' to contend with, although some of these factors are common between specific traits.…”
Section: Factor #I: Modalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ito et al [17] commented on how researchers seek "new biometric traits to enhance the accuracy and convenience of biometric recognition" suggesting that modalities differ in their performance. Each modality is unique and with that brings an assortment of 'influencing factors' to contend with, although some of these factors are common between specific traits.…”
Section: Factor #I: Modalitiesmentioning
confidence: 99%
“…While exploring recent advancements in biometric recognition, Ito et al [17] states, "biometric techniques [that are] to be used in the practical system depend heavily on application requirements".…”
Section: Factor #V: System Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several biometric characteristics (e.g., DNA, face, and palmprint) that can be exploited in authentication systems [1]. Each one has its own pros and cons, and therefore there is no single optimal characteristic that satisfies all application requirements [2]. Consequently, based on the constraints and conditions of the operational mode, one or more biometric characteristics can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…have been commercially available and used in access control, ATM, etc. K. Ito et al [1] identified several special features as biometric traits such as: Universality, Uniqueness, Permanence and Measurability.…”
Section: Introductionmentioning
confidence: 99%